Innovation translates into antidepressant effectiveness. - Goodwin, G (2008)
Unipolar depression is a major cause of disability in developed societies. There is significant unmet need because existing treatments are neither as effective nor as free of adverse effects as we would hope. Agomelatine is a new antidepressant with a novel profile of pharmacological action. Its efficacy in major depression has been reported in short-term placebo-controlled trials and in direct head-to-head comparison with existing products. The pooling of data from the agomelatine short-term studies allows analysis of sub-groups within the study populations. There is a trend for a larger effect size to be seen with more severely ill patients as a consequence of placebo responses falling. Efficacy is also reported in the maintenance of effect seen after clinical response in a recently completed relapse prevention study, analysed initially after 6 months. What is unusual, certainly compared with the selective serotonin reuptake inhibitors (SSRIs) and venlafaxine, is the clear absence of an excess of early relapses soon after agomelatine withdrawal. This parallels the absence of an immediate withdrawal effect seen in the pattern of subjective symptoms in another study. It underlines the distinct and novel pharmacological properties of the product, and has evident clinical advantages for the patient. Agomelatine is well tolerated in other respects; only occasional dizziness emerges at significant rates higher than with placebo in the controlled data.